Growth Response, Flavonoid Content, and Antioxidant Activity of Mustard Microgreen under Reduced Water Availability - An'nisa An'nisa; Wahyu Harso; Oryyani Lambui; Prismawiryanti Prismawiryanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Mustard (Brassica juncea L.) has often been cultivated as a microgreen. Investigation into the impact of water stress effects on mustard in the microgreen stage is currently limited. The objective of this study was to assess the effect of reduced water availability on growth performance, flavonoid concentration, and antioxidant potential in mustard microgreens. Samples used to assess plant growth, flavonoid content, and antioxidant activity were collected from mustard plants grown in growth media under water availability of 90%, 70%, and 50% of field capacity. All acquired data were further evaluated by applying a one-way ANOVA. Reducing water availability to 50% field capacity did not impact growth, but it did enhance flavonoid content and antioxidant capacity. Peak values occurred at 70% of field capacity, with flavonoid content positively correlated with antioxidant activity. A water availability of 70% field capacity can be recommended as the optimal condition for producing mustard microgreens, as it effectively increases flavonoid content without inhibiting plant growth. This study confirms that growth parameters do not always accurately reflect the functional quality of plants; therefore, the evaluation of horticultural crops needs to include aspects related to secondary metabolites.